1985
DOI: 10.1139/v85-399
|View full text |Cite
|
Sign up to set email alerts
|

(S)-2,2,5,5-Tetramethylthiazolidine-4-carboxylic acid: a compound which exists in the amino acid rather than the zwitterion form

Abstract: The X-ray crystal structure of (S)-2,2,5,5-tetramethylthiazolidine-4-caboxyic acid, b, has been determined. Crystals are monoclinic, P 2 , , with cell dimensions a = 11.351(4) b = 8.303(2), c = 11.969(3) A, P = 116.69(2)", and Z = 4. The structure was solved by standard methods and refined to RI = 0.0774, R2 = 0.0670 for 2388 independent reflections.Compound 1 exists in the amino-acid form as shown by two distinctly different C-0 bond lengths, 1.209 and 1.309 A, typical of the COOH group, and by the positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…The OIN202C3 unit is planar, consistent with an sp 2 N atom, but the angles at N2 are markedly distorted from the ideal 120 ° . While the internal ring angle is close to the expected value, the angle between the N2-O2 group and the N2-O1 single bond is closed up, with consequent increase in the angle between the two double bonds, features which we and others have observed in carboxylic acids (Howard-Lock, Lock & Smalley, 1985;Howard-Lock, Lock, Martins, Smalley & Bell, 1986;Howard-Lock, Lock, Martins, Faggiani & Duarte, 1987). The N2-C3-C4 angle is also greater than 120 ° [125.5 (3) ° ] consistent with some conjugation between N2-C3 and C3-C4.…”
supporting
confidence: 82%
“…The OIN202C3 unit is planar, consistent with an sp 2 N atom, but the angles at N2 are markedly distorted from the ideal 120 ° . While the internal ring angle is close to the expected value, the angle between the N2-O2 group and the N2-O1 single bond is closed up, with consequent increase in the angle between the two double bonds, features which we and others have observed in carboxylic acids (Howard-Lock, Lock & Smalley, 1985;Howard-Lock, Lock, Martins, Smalley & Bell, 1986;Howard-Lock, Lock, Martins, Faggiani & Duarte, 1987). The N2-C3-C4 angle is also greater than 120 ° [125.5 (3) ° ] consistent with some conjugation between N2-C3 and C3-C4.…”
supporting
confidence: 82%
“…(1.745(5) A) is significantly shorter than C5-S1 (1.827(4) A), and the former distance lies outside the ranGe we have observed in thiazolidine rings (1.784(5)-1.869(6) A) (14,15). The difference is in the expected direction since an sp' carbon atom is smaller than an sp3 carbon atom (0.743 vs. 0.763 A) (16).…”
Section: Discussionmentioning
confidence: 63%
“…In L-cysteine it has been assigned to 678 cm and it has been concluded that substituents on carbon atoms adjacent to sulfur cause a decrease in the stretching frequency of the C-S bond (7). Bands in the region of 680 and 600 cm, and 630 and 540 cm, are so assigned.…”
Section: Resultsmentioning
confidence: 99%